Utilization of ICE Institute as one of the MOOCs for universities in Indonesia - Julia Permatasari Nasution; Luna Ade Yunisa; Padil Putra Padillah (Himpunan Pengembang Kurikulum Indonesia, 2024)
The current popularity of online education provides certification opportunities by utilizing strategies such as blockchain, micro-credentials, and digital credentials for degree-awarding. Recognizing the seriousness of this, the Indonesian government has established the Indonesia Cyber Education Institute (ICE Institute) under the auspices of the Ministry of Education and Culture and the Ministry of Research and Technology, managed by the Open University to improve and guarantee the quality of online education incorporating blockchain, technology to issue certificates, ensuring a transparent registration and verification system. This significant step is transforming higher education in Indonesia, aligning it with the demands of Industry 4.0. This research focuses on exploring the architecture and functionality of ICE Institute, emphasizing its role as a quality assurance facility for online education in Indonesia. It also examines the user experience, enrollment process, and the impact of ICE Institute on the competency development of Educational Technology students based on an interview with a student. The research method used a qualitative descriptive approach through interviews. The findings of this study show that despite the challenges, ICE Institute is a crucial player in shaping the landscape of online education in Indonesia, positively contributing to accessibility, quality, and relevance in higher education. Abstrak Popularitas pendidikan online saat ini memberikan peluang sertifikasi dengan memanfaatkan strategi seperti blockchain, kredensial mikro, dan kredensial digital untuk penganugerahan gelar. Menyadari keseriusan tersebut, pemerintah Indonesia telah mendirikan Indonesia Cyber Education Institute (ICE Institute) di bawah naungan Kementerian Pendidikan dan Kebudayaan dan Kementerian Riset dan Teknologi, yang dikelola oleh Universitas Terbuka untuk meningkatkan dan menjamin kualitas pendidikan online yang menggabungkan teknologi blockchain untuk menerbitkan sertifikat, memastikan sistem pendaftaran dan verifikasi yang transparan. Langkah signifikan ini mentransformasikan pendidikan tinggi di Indonesia, menyelaraskannya dengan tuntutan Industri 4.0. Penelitian ini berfokus untuk mengeksplorasi arsitektur dan fungsi ICE Institute, menekankan perannya sebagai fasilitas penjaminan mutu pendidikan online di Indonesia. Selain itu juga menggali pengalaman pengguna, proses pendaftaran, dan dampak ICE Institute terhadap pengembangan kompetensi mahasiswa Teknologi Pendidikan berdasarkan wawancara dengan seorang mahasiswa. Metode penelitian menggunakan pendekatan deskriptif kualitatif melalui wawancara. Hasil temuan penelitian ini menunjukkan bahwa terlepas dari tantangan-tantangan yang ada, ICE Institute menjadi pemain kunci dalam membentuk lanskap pendidikan online di Indonesia, memberikan kontribusi positif terhadap aksesibilitas, kualitas, dan relevansi dalam pendidikan tinggi. Kata Kunci: ICE Institute; MOOCs; pembelajaran terbuka